AB ve Orta Doğu - Çayhan, B. Esra (Fırat University, 2011)
Bu çalışma 6 Mayıs 2011 tarihinde Fırat Üniversitesi Orta Doğu Araştırmaları Merkezinde düzenlenmiş bulunan “AB ve Orta Doğu” başlıklı konferansın özet metni olup, AB’nin geniş kapsamlı Orta Doğu ilişkilerini Akdeniz politikası özelinde irdelemektedir

This text is a summary of “The EU and the Middle East” conference which was held at the Middle East Research Centre of Fırat University on 6 May 2011. It assesses the EU’s relations with the Middle East with special emphasis on the EuroMediterranean Partnership
The EU and the Middle East